Early postdenervation depolarization develops faster at endplates of hibernating golden hamsters where spontaneous quantal and non-quantal acetylcholine release is very small - Moravec, Jan; Vyskocil, Frantisek (Neuroscience research, 2005)
The hyperpolarization produced by the application of curare to the postsynaptic membrane of the diaphragm neuromuscular synapse (H-effect) is a measure of non-quantal release (NQR) of acetylcholine (ACh) from the motor nerve ending. In mouse diaphragm, H-effect was 9.3 mV, significantly lower in awake hamsters (7.1 mV) and very small (1.1 mV) in hibernating hamsters. Also, the initial resting membrane potential (RMP) after dissection was highest in mouse (81.5 mV, inside negative), significantly smaller in awake hamsters (77.9 mV) and lowest in hibernating hamsters (75.1 mV). The early postdenervation depolarization of muscle fiber RMP to about 66-68 mV developed with half-decay time (T1/2) of 120 min in mouse, more rapidly in active hamsters (T1/2=60 min) and even faster in hibernating hamsters (T1/2=25 min) muscles. This reciprocal correlation between the H-effect and the rate of early depolarization indicates that non-quantal release is important for maintaining the resting membrane potential [Vyskocil, F. 2003. Early postdenervation depolarization is controlled by acetylcholine and glutamate via nitric oxide regulation of the chloride transporter. Neurochem. Res. 28, 575-585]. The amplitude of H-effect in mouse and hamster was proportional to the spontaneous quantal release. The frequency of miniature endplate potentials was highest in mouse (1.6 s-1), much smaller in awake hamsters (0.51 s-1) and very small in hibernating hamsters (0.08 s-1). This is in accordance with the idea that non-quantal release depends on the number of vesicles fused with the presynaptic membrane during quantal release [Edwards et al., 1985; Ferguson, S.M., Savchenko, V., Apparsundaram, S., Zwick, M., Wright J., Heilman, C.J., Yi, H., Levey, A.I., Blakely R.D. Vesicular localization and activity-dependent trafficking of presynaptic choline transporters. J. Neurosci. 23 (2003) 9697-9709].
Keywords: křečci praví; neparametrická statistika; techniky in vitro; sympatektomie; nedepolarizující myorelaxancia; kurare; acetylcholin; Female; analýza rozptylu; Analysis of Variance; nervosvalová ploténka; zvířata; myši; časové faktory; Mice; Acetylcholine; hibernace; ženské pohlaví; Hibernation; Male; Sympathectomy; bránice; Excitatory Postsynaptic Potentials; In Vitro Techniques; Statistics, Nonparametric; Cricetinae; Neuromuscular Nondepolarizing Agents; Animals; Diaphragm; Membrane Potentials; excitační postsynaptické potenciály; mužské pohlaví; membránové potenciály; Motor Endplate; Time Factors; Curare